PERLINDUNGAN HUKUM MAHASISWA TERHADAP DEGRADASI NILAI AKREDITASI PROGRAM STUDI DAN PERGURUAN TINGGI - Miftakhul Huda (Jurnal HUKUM BISNIS, 2022)
Accreditation of study programs and universities is still very valuable for students, especially for continuing careers after studying in college. Various agencies require study program accreditation scores to be able to participate in the selection of job vacancies. Students who initially register at a university with good accreditation, do not have a guarantee that when they graduate their study program accreditation does not decrease. Meanwhile, the accreditation value used is the accreditation value at the time of graduation from the university. Therefore, the position of students is very vulnerable to be harmed by changes in the value of accreditation, especially those changes caused by education management errors. It is necessary to clarify the legal position of each party so that it is clear who is responsible and what legal remedies can be taken. This research was conducted using a normative juridical method with a statutory and conceptual approach. The results of this study are that students can file a lawsuit for unlawful acts at the District Court or a lawsuit Onrechtmatige Overheidsdaad at the State Administrative Court. Keywords: Student, Higher Education, Accreditation